THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS MEDIATION VARIABLES AT PT. SULSELBAR BANK JENEPONTO DISTRICT BRANCH - Muhammad Idrus Taba; Nurdjanah Hamid; Fatimah Nurhudasari (Scientia integritas Utama, 2023)
This study aims to determine the influence of leadership style and organizational culture on employee performance through job satisfaction as a mediating variable at PT. Bank SulselBar Jeneponto Regency Branch. This research was conducted at PT Bank Sulselbar Jenepont Branch by taking information from employees, with a total sample of 43 employees. Data were analyzed using a quantitative approach and processed using the SPSS version 22 application. The results of this study indicate that leadership style has an effect on job satisfaction and organizational culture has an effect on job satisfaction, in contrast to job satisfaction which has no significant effect on performance. significant effect on employee performance. Then, based on the results of the intervention, the influence of leadership style and organizational culture has a significant effect on employee performance through job satisfaction. This shows that job satisfaction can be a link between leadership style and organizational culture on employee performance